ANALISIS PENGGUNAAN MEDIA LAYANAN BIMBINGAN DAN KONSELING DI SMP NEGERI 3 SIMPANG HILIR - Saputra, Yoga; Asrori, Muhammad; Halida, Halida (Universitas Tanjungpura, 2024)
This research aims to describe the analysis of the use of guidance and counseling service media at SMP Negeri 3 Simpang Hilir. The form of research uses a study survey. The sample in this study was 44 students in class VIII A and VIII B. The research method used is descriptive quantitative. Data collection using indirect communication techniques, direct communication and documentary study techniques. Data analysis uses percentage correction. The results of the research show that the analysis of the use of media for guidance and counseling services for classes VIII A and VIII B at SMP Negeri 3 Simpang Hilir with the percentage of media use for guidance and counseling services is generally categorized as good with a presentation of 70%. Specifically, it is concluded as follows: The silent projection media group is categorized as good with a percentage of 69.57%. The film media group is categorized as good with a percentage of 70.85%. Based on the description above, in general, the analysis of the use of guidance and counseling service media is still at the stage of being successfully carried out VIII A and VIII B at SMP Negeri 3 Simpang Hilir.